Design, development and evaluation of an automated drip irrigation system - NAVNEET SHARMA; Dr. Abdul Hakkim V. M (Guide) (Tavanur 2014 DEPARTMENT OF LAND &WATER RESOURCES AND CONSERVATION ENGINEERING)
the system was installed in the field for a season under the crop amaranthus and it was observed that the system is working properly and the motor gets switched '' on'' and ' off '' automatically with respect to pre-set value of moisture content.
Design, development and evaluation of an automated drip irrigation system